EXPERIMENTING WITH KIDS : 50 AMAZING SCIENCE PROJECTS YOU CAN PERFORM ON YOUR CHILD AGES 2-5 - Gallagher, Shaun (London, UK : TarcherPerigee, an imprint of Penguin Random House LLC, 2020)
"Transform your child into a science project with these fun, simple experiments. Re-create landmark studies in child development in your own home and watch your little one achieve developmental milestones in real time with this fascinating hands-on guide. Whether your child is just beginning to speak in sentences or is on their way to kindergarten, these easy and surprising projects will help you to see the world through your child's eyes--and also give you the tools to help them master new skills as they grow. Covering ages two through five, the experiments reveal research-backed insights about different areas of mental, physical, and social growth. Some examples include: Understanding language syntax; Learning to pick up the rules of a game without being told; Developing the impulse to lie; Testing memory For any parent who looks at their young child and thinks, "What on earth is going on in there?" this book will help you find out!"
Keywords: Child development -- Study and teaching; Toddlers Development; Science projects